REORIENTASI PENDIDIKAN ISLAM (Menimbang Tarbiyah Syari’ah Sebagai Alternatif) - Amrizal Amrizal (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2012)
Tarbiyah Syar’iyah is oriented education in accordance with the objective syar’i (maqasid syari’ah). Referring to the theory of maqashid syari’ah, the Islamic education should be oriented to: 1) The development of religion and religious sciences/religius (hifz al-din) and, 2) concept of humanitarian/humanis (hifz al-nafs), 3) rational and development of human intelligence (hifz al-‘aql), 4) maintenance of the interests of families, communities and national or social perpective (hifz al-nasl and hifz al-ummah), 5)insightful economic and welfare development (hifz al-mal), 6) insightful achievements in improving self-esteem people ( hifz al-‘aradh), 7) concept pragmatic (jalb al-mashalih), and 8) solutif-anticipatory (dar al-mafasid)